Cyanobacteria Recent Advances in Taxonomy and Applications - Hozzein, Wael N. (IntechOpen, 2022)
Cyanobacteria are oxygenic organisms that play crucial roles in the cycles of carbon, nitrogen, and oxygen. They are ideal model organisms for studying photosynthesis, nitrogen fixation, and other biological processes. In addition, cyanobacteria are well recognized for their potential for a variety of biotechnological applications. This book presents a comprehensive overview of this interesting and useful group of bacteria. Chapters discuss such topics as the molecular methods applied for identifying freshwater toxigenic cyanobacteria, the diverse industrial applications of cyanobacteria, the potential of cyanobacteria in wound healing, the production of a novel hemoglobin by Synechocystis sp. PCC 6803, and the diversity, distribution, and applications of cyanobacteria in the Brazilian coastline.